Accounting information systems in the blockchain era. (19th February 2021) - Fullana, Olga; Ruiz, Javier
In this paper we analyse the advantages that the application of blockchain technology brings to accounting information systems (AIS), but also highlight the potential issues with its use. We examine the use of blockchain against the background of the historical evolution of AIS and explain the operational fit of this technology in AIS. We then analyse the pros and cons of the highly probable use of blockchain technology in AIS. For this purpose, we review the relevant contributions on this subject in the accounting academic literature to date and classify them into four categories on the basis of their focus: governance, transparency and trust; continuous audit; smart contracts; and roles of accountants and auditors. We also analyse the early reactions of the accounting industry and regulators to this new technological environment.